Design, development and management of UniMAP's green transportation system / Malek Khalaf Salem Albezuirat. - Albezuirat, Malek Khalaf Salem (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2015)
This study aims to apply proper Project Management (PM) principles in the execution of UniMAP's Green Transportation Design and Development Project (UGTDDP) and Smart Vehicle (SV).